Interference with the retinoic acid signalling pathway inhibits the initiation of teeth and caudal primary scales in the small-spotted catshark Scyliorhinus canicula - Isabelle Germon; Coralie Delachanal; Florence Mougel; Camille Martinand-Mari; Mélanie Debiais-Thibaud; Véronique Borday-Birraux (PeerJ, 2023)
The retinoic acid (RA) pathway was shown to be important for tooth development in mammals, and suspected to play a key role in tooth evolution in teleosts. The general modalities of development of tooth and “tooth-like” structures (collectively named odontodes) seem to be conserved among all jawed vertebrates, both with regard to histogenesis and genetic regulation. We investigated the putative function of RA signalling in tooth and scale initiation in a cartilaginous fish, the small-spotted catshark Scyliorhinus canicula. To address this issue, we identified the expression pattern of genes from the RA pathway during both tooth and scale development and performed functional experiments by exposing small-spotted catshark embryos to exogenous RA or an inhibitor of RA synthesis. Our results showed that inhibiting RA synthesis affects tooth but not caudal primary scale development while exposure to exogenous RA inhibited both. We also showed that the reduced number of teeth observed with RA exposure is probably due to a specific inhibition of tooth bud initiation while the observed effects of the RA synthesis inhibitor is related to a general delay in embryonic development that interacts with tooth development. This study provides data complementary to previous studies of bony vertebrates and support an involvement of the RA signalling pathway toolkit in odontode initiation in all jawed vertebrates. However, the modalities of RA signalling may vary depending on the target location along the body, and depending on the species lineage.